PENGARUH KUALITAS INFORMASI, PERSEPSI RISIKO DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE (STUDI PADA KONSUMEN TOKOPEDIA DI KABUPATEN BANTUL) - Fahkrul Eka Saputra; Susanto Susanto; Muinah Fadhilah (Program Studi Manajemen, 2018)
This study aims to determine: (1) the effect of information quality, risk perception, and trust on purchasing decisions on Tokopedia consumers in Bantul Regency (2) the effect of information quality on purchasing decisions on Tokopedia consumers in Bantul Regency (3) the effect of risk perceptions on decisions purchases at Tokopedia consumers in Bantul Regency (4) the effect of trust on purchasing decisions on Tokopedia consumers in Bantul Regency. This research is a quantitative research. The population in this study are consumers who have purchased products or goods for at least the last six months on Tokopedia. The sampling technique used purposive sampling with a total of 100 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The results showed that: (1) there was a positive and significant influence on the quality of information on purchasing decisions at Tokopedia, as evidenced by the t-count value of 3.138; the significance value is 0.002 <0.05; and a regression coefficient of 0.214; (2) there is a positive and significant impact on risk perceptions on purchasing decisions on Tokopedia, as evidenced by the t value of 4,750; the significance value is 0.000 <0.05; and a regression coefficient of 0.479; (3) there is a positive and significant effect of trust on purchasing decisions on Tokopedia, as evidenced by the t value of 2.227; the significance value is 0.028 <0.05; and a regression coefficient of 0.128; (5) there is a positive influence on information quality, risk perception, and trust in purchasing decisions on Tokopedia, as evidenced by the calculated F value of 20.096 with a significance of 0.00 <0.05.